2014
DOI: 10.3389/fphys.2014.00271
|View full text |Cite
|
Sign up to set email alerts
|

A deficiency of apoptosis inducing factor (AIF) in Harlequin mouse heart mitochondria paradoxically reduces ROS generation during ischemia-reperfusion

Abstract: Background and Aims: AIF (apoptosis inducing factor) is a flavin and NADH containing protein located within mitochondria required for optimal function of the respiratory chain. AIF may function as an antioxidant within mitochondria, yet when released from mitochondria it activates caspase-independent cell death. The Harlequin (Hq) mouse has a markedly reduced content of AIF, providing an experimental model to query if the main role of AIF in the exacerbation of cell death is enhanced mitochondrial generation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
(107 reference statements)
1
7
0
Order By: Relevance
“…Under different stimuli, PARP-1 [poly (ADP-ribose) polymerase-1] activation triggers mitochondrial AIF release and translocation to the nucleus [5052]. PARP-1 activation produces PAR in the nucleus, which is released into the cytosol and colocalizes with the mitochondria to induce AIF release [53].…”
Section: Discussionmentioning
confidence: 99%
“…Under different stimuli, PARP-1 [poly (ADP-ribose) polymerase-1] activation triggers mitochondrial AIF release and translocation to the nucleus [5052]. PARP-1 activation produces PAR in the nucleus, which is released into the cytosol and colocalizes with the mitochondria to induce AIF release [53].…”
Section: Discussionmentioning
confidence: 99%
“…ROS and peroxynitrite, which are part of ischemia and reperfusion injury at the end lead to nitrosylated proteins, DNA damage, AIF and caspase‐3 activation. In a very recent study it was demonstrated in a mouse model of reduced AIF expression that cardiac ischemic/reperfusion injury was significantly attenuated if AIF translocation was shut down even if ROS levels were not altered . Thus, AIF relocation seems to be important in the development of tissue damage.…”
Section: Discussionmentioning
confidence: 99%
“…When the cellular antioxidant capacity is overwhelmed, ROS concentrations may increase dramatically and the resulting oxidative stress can cause substantial cell damage and ultimately cell death. Hence, both oxidative stress originating from mitochondrial activity and mitochondrial dysfunction ensuing from related oxidative damage have been shown to play important roles in aging and the pathogenesis of various disease states such as ischemia, neurodegeneration, diabetes and atherosclerosis (reviewed in [ 2 , 3 , 4 ]).…”
Section: Introductionmentioning
confidence: 99%